KEWAJIBAN NAFKAH IDDAH : PERSPEKTIF HUKUM ISLAM DAN REALITAS SOSIAL DI MANDAILING NATAL - Nst, Andri muda (Program Studi Hukum Keluarga Islam STAIN Mandailing Natal, 2025)
This research examines the obligation of Iddah alimony from the perspective of Islamic law and socio-cultural realities in Mandailing Natal. Nafkah Iddah is the responsibility of the ex-husband towards the ex-wife during the Iddah period, which aims to ensure post-divorce social welfare and protection. Although this obligation has been clearly regulated in the Qur'an, hadith, and positive law in Indonesia, its implementation in Mandailing Natal still faces various challenges. This research uses a qualitative approach with literature study and field observation methods to analyse the factors that influence the fulfilment of Iddah alimony, including social, cultural, economic, and law enforcement aspects. The results show that the low compliance with Iddah alimony obligations is caused by economic factors, lack of religious understanding, weak law enforcement, and the influence of local customary norms that tend to shift responsibility for women in the Iddah period to the woman's family. In addition, modernisation and urbanisation have changed people's perspectives on women's rights, but local cultural norms are still dominant. This research recommends increased legal literacy, synergy between law and custom, strengthened law enforcement, and economic support for post-divorce women to ensure the fulfilment of their rights in accordance with the principles of justice and protection in Islamic law.